The Emerging Role of Zinc in the Pathogenesis of Multiple Sclerosis - Choi, Bo Young (Int J Mol Sci, 2017)
Our lab has previously demonstrated that multiple sclerosis-induced spinal cord white matter damage and motor deficits are mediated by the pathological disruption of zinc homeostasis. Abnormal vesicular zinc release and intracellular zinc accumulation may mediate several steps in the pathophysiological processes of multiple sclerosis (MS), such as matrix metallopeptidase 9 (MMP-9) activation, blood-brain barrier (BBB) disruption, and subsequent immune cell infiltration from peripheral systems. Oral administration of a zinc chelator decreased BBB disruption, immune cell infiltration, and spinal white matter myelin destruction. Therefore, we hypothesized that zinc released into the extracellular space during MS progression is involved in destruction of the myelin sheath in spinal cord white mater and in generation of motor deficits. To confirm our previous study, we employed zinc transporter 3 (ZnT3) knockout mice to test whether vesicular zinc depletion shows protective effects on multiple sclerosis-induced white matter damage and motor deficits. ZnT3 gene deletion profoundly reduced the daily clinical score of experimental autoimmune encephalomyelitis (EAE) by suppression of inflammation and demyelination in the spinal cord. ZnT3 gene deletion also remarkably inhibited formation of multiple sclerosis-associated aberrant synaptic zinc patches, MMP-9 activation, and BBB disruption. These two studies strongly support our hypothesis that zinc release from presynaptic terminals may be involved in multiple sclerosis pathogenesis. Further studies will no doubt continue to add mechanistic detail to this process and with luck, clarify how these observations may lead to development of novel therapeutic approaches for the treatment of multiple sclerosis.